Protocol for evaluation of a virtual wheelchair simulator in assessing mobility skills and cognitive abilities in diverse populations: A multicentric mixed-methods pilot study - Débora Pereira Salgado; Caroline Valentini de Queiroz; Eduardo Lázaro Martins Naves; Yuansong Qiao; Sheila Fallon (PLoS ONE, 2025)
Background Current wheelchair acquisition, prescription, and training programs often require comprehensive assessments integrating both power mobility skills and cognitive abilities. While wheelchair simulators offer promise for these assessments, but they have not been fully validated. Objective This study aims to develop and refine a protocol for evaluating the feasibility, reliability and preliminary validity of virtual wheelchair simulator metrics in assessing users’ current power mobility skills and cognitive abilities, following STARD guidelines. Reference standards include the self-report Wheelchair Skill Test (WST), Power Mobility Road Test (PMRT) and the Montreal Cognitive Assessment (MoCA). Methods This multicentric, mixed-methods pilot study will recruit participants with mobility disabilities, a control group of individuals without disabilities, and healthcare professionals to use a virtual wheelchair simulator. Healthcare professionals will evaluate the simulator’s assessments and provide expert feedback on the protocol. Quantitative data will include simulator-derived performance metrics compared to reference standards, and physiological data (e.g., heart rate, skin conductance, temperature, inter-beat-intervals, accelerometer and eye-gaze tracking). Qualitative data (semi-structured interviews) will capture user experiences and insights for protocol refinement. The Quality of Experience (QoE) evaluation framework will assess cognitive workload (NASA-TLX and PAAS), usability (System Usability Scale), immersion (IGroup Presence Questionnaire), and emotion (Self-Assessment Manikin). Data analysis will include correlation analysis, regression models, thematic analysis, and statistical tests (e.g., independent t-tests, Mann-Whitney U tests) to compare simulator-based performance across groups. Discussion This pilot study seeks to fill critical gaps in current wheelchair training and prescription methods by exploring the use of a virtual simulator to objectively assess both cognitive abilities and power mobility skills. Integrating the QoE assessment framework will provide insights into user interactions, ensuring that the simulator supports tailored training and improve user outcomes in mobility, and safety. Future research may extend this protocol to clinical settings to further evaluate its applicability and effectiveness.